Monitoring jako narzędzie diagnozy i oceny rozwoju przedsiębiorstwa - Barczak, Beata; Walas-Trębacz, Jolanta (Monitoring as instrument of diagnosis and evaluation of development enterprise, 2005)
The paper contains the review of interpretation idea monitoring and functions and tasks, which should attend monitoring in the enterprise. The paper describes also specific characters of monitoring as instrument helping in the function diagnosis and evaluation different domains of enterprise. Monitoring is helpful in the identification opportunities and threats existing in environment. The paper comprises synthetic presentation of selected domains and areas of application monitoring in the enterprise and methods, which him help.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 192-200